2010
DOI: 10.1002/nbm.1588
|View full text |Cite
|
Sign up to set email alerts
|

A fast black‐blood sequence for four‐dimensional cardiac manganese‐enhanced MRI in mouse

Abstract: The increasing number of mouse models of cardiac diseases requires improvements in the current MRI tools. Anatomic and functional cardiac phenotyping by MRI calls for both time and space resolution in three dimensions. Black-blood contrast is often needed for the accurate delineation of myocardium and chambers, and is consistent with manganese contrast enhancement. In this article, we propose a fast, three-dimensional, time-resolved (four-dimensional), black-blood MRI sequence that allows mouse heart imaging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…To demonstrate the efficiency of the current method in the case of cardiac disease, mice with surgically induced MI were injected with 60 μL of MnCl 2, corresponding to a dose of 86 µmol kg −1 . Manganese ions, as previously demonstrated in the literature , did not penetrate the infarcted region, leading to a decrease in the T 1 in healthy regions of the myocardium without changing the T 1 of the infarcted areas. As shown in Figure (a), the current protocol allowed us to visualize the myocardial infarct in 3D with high spatial resolution.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…To demonstrate the efficiency of the current method in the case of cardiac disease, mice with surgically induced MI were injected with 60 μL of MnCl 2, corresponding to a dose of 86 µmol kg −1 . Manganese ions, as previously demonstrated in the literature , did not penetrate the infarcted region, leading to a decrease in the T 1 in healthy regions of the myocardium without changing the T 1 of the infarcted areas. As shown in Figure (a), the current protocol allowed us to visualize the myocardial infarct in 3D with high spatial resolution.…”
Section: Resultssupporting
confidence: 52%
“…Between each injection, a delay of 15 min was necessary to reach the maximum Mn 2+ infusion in the heart, as previously demonstrated by Lefrançois et al . .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2A). MEMRI has also been applied in an IR model with a 3 T clinical scanner and an approximately 10-fold higher dose MnCl 2 (30) and in a PO model using a 3D black-blood sequence (31). Both studies confirmed that infarct size and location on MEMRI were in agreement with TTC staining.…”
Section: Manganese-enhanced Mrimentioning
confidence: 98%